Heavy metals in the landscape components of the Kalmykia - L. Ch. Sangadzhieva; O. S. Sangadzhieva; Zh. D. Davaeva; V. P. Chodyacov; Z. B. Badmaeva (Юг России: экология, развитие, 2015)
The concentrations of heavy metals (Cr, Co, Ni, Cu, Zn, Cd, Pb) in the soil of nord-west part of Precaspian low-land and their subsequent distribution over the trophic chain: plant fodder - sheep are investiqаtеd. It was revealed that the highest biogenic accumulation is characteristic of Zn and Cu at all the levels of trophic chain. An increase in the transition coefficients for the most toxic elements Pb, Cd is observed, which is an evidence of their accumulation in the higher levels of trophic chain.